Isolation and cytotoxic investigation of new carbazole alkaloids from Murraya koenigii (Linn.) Spreng - Tan, Siow Ping; Ali, Abdul Manaf; Nafiah, Mohd Azlan; Awang, Khalijah; Ahmad, Kartini (Elsevier, 2015)
Six new carbazole alkaloids, murrastanine-A (1), murrastinine-A, -B, -C (2-4), murrayatanine-A (5) and bismahanimboline (6), were isolated from the bark and leaves of Murraya koenigii (Linn.) Spreng along with 24 known carbazole alkaloids. The structure of these compounds were elucidated by extensive spectroscopic analysis. Murrastinine-C (4) and murrayatanine-A (5) exhibited cytotoxic activity against HL-60 and HeLa (CD50<20 μg/mL) via MTT assay.